Portrayals of branded soft drinks in popular American movies: a content analysis - Bell Robert A; Townsend Marilyn; Cassady Diana; Watnik Mitchell (BMC, 2006)
Abstract Background This study examines the portrayals of soft drinks in popular American movies as a potential vehicle for global marketing and an indicator of covert product placement. Methods We conducted a content analysis of America's top-ten grossing films from 1991 through 2000 that included portrayals of beverages (95 movies total). Coding reliabilities were assessed with Cohen's kappa, and exceeded 0.80. If there was at least one instance of branding for a beverage, the film was considered having branded beverages. Fisher's exact test was used to determine if soft drink portrayals were related to audience rating or genre. Data on the amount of time soft drinks appeared onscreen was log transformed to satisfy the assumption of normality, and analyzed using a repeated measures ANOVA model. McNemar's test of agreement was used to test whether branded soft drinks are as likely to appear or to be actor-endorsed compared to other branded beverages. Results Rating was not associated with portrayals of branded soft drinks, but comedies were most likely to include a branded soft drink (p = 0.0136). Branded soft drinks appeared more commonly than other branded non-alcoholic beverages (p = 0.0001), branded beer (p = 0.0004), and other branded alcoholic beverages (p = 0.0006). Actors consumed branded soft drinks in five times the number of movies compared to their consumption of other branded non-alcoholic beverages (p = 0.0126). About half the revenue from the films with portrayals of branded soft drinks come from film sales outside the U.S. Conclusion The frequent appearance of branded soft drinks provides indirect evidence that product placement is a common practice for American-produced films shown in the U.S. and other countries.